Leg Length Measurement: Review - Daria A. Petrova; Vladimir M. Kenis (Travmatologiâ i Ortopediâ Rossii, 2022)
Background. Measurement of the length of the lower extremities is an important part of the assessment of the musculoskeletal system. If there is a discrepancy in the length of the legs, the accuracy of the measurement technique will determine the choice of further tactics for treating the patient. However, to date, there is no consensus among experts regarding the optimal and accurate method for assessing this clinical condition.